Transparent functional nanocomposite films based on octahedral metal clusters: synthesis by electrophoretic deposition process and characterization. Issue 3 (6th March 2019) - Thi Kim Nguyen, Ngan; Dubernet, Marion; Matsui, Yoshio; Wilmet, Maxence; Shirahata, Naoto; Rydzek, Gaulthier; Dumait, Noée; Amela-Cortes, Maria; Renaud, Adèle; Cordier, Stéphane; Molard, Yann; Grasset, Fabien; et al.
Abstract : Transparent optical thin films have recently attracted a growing interest for functional window applications. In this study, highly visible transparent nanocomposite films with ultraviolet (UV)-near-infrared (NIR)-blocking capabilities are reported. Such films, composed of Mo6 and Nb6 octahedral metal atom clusters (MC) and polymethylmethacrylate polymer (PMMA), were prepared by electrophoretic deposition on indium tin oxide-coated glass (ITO glass). PMMA was found to improve both the chemical and physical stability of Mo6 and Nb6 MCs, resulting in a relatively homogeneous distribution of the clusters within the PMMA matrix, as seen by microstructural observations. The optical absorption spectrum of these transparent MC@polymer nanocomposite films was marked by contributions from their Mo6 and Nb6 -based clusters (absorption in the UV range) and from the ITO layer on silica glass (absorption in the NIR range). Mo6 @PMMA nanocomposite films also exhibited excellent photoluminescence properties, which were preserved even after exposure to 50°C at a relative humidity of 70% for one month. These films cumulate high transparency in the visible range with remarkable UV-NIR blocking properties and represent interesting candidates for functional glass application.